Segmentation, Targeting, dan Positioning Studio Tato di Surabaya dalam Perkembangan Gaya Hidup - Wahyudi, Anang Tri (Nirmana, 2013)
This study attempts to examine in depth the influence of lifestyle on the orientation of recipients (tattoo users) to the art of tattooing, which is independent of the value of a valuable commodity, and explore the extent to which the process of tattoo studios’ segmentation, targeting, and positioning in managing a tattoo studio. This study uses qualitative research methods with interpretive phenomenological foundation of thinking, which is oriented to truth that is subjective to informants, which consists of a tattoo studio tattooist and managers who have more than five years of experience, and the recipient women and men under the age of 30. The development of post-modern lifestyle is synonymous with consumer culture, which affects the orientation of recipients towards tattoos as works of art, a medium of expression, search for identity, and part of fashion accessories, therefore tattoos become works of art that have commodity value. The existing tattoo studios already have market segments, target markets, positioning, and clear marketing strategy, however there are some tattoo studios that do not determine their market segments and target goals. They tend to flow and follow the situation and market conditions. Several factors that affect the condition and management of tattoo studios today are environmental factors, resource constraints, and tattoos as art products that are homogeneous.